Male vs. Female Perception of Problems Highlighted for Solving and Innovating - Karine Oganisjana; Konstantins Kozlovskis (Journal of Systemics, Cybernetics and Informatics, 2021)

(untitled)
Problem driven approach with customer engagement is argued to be one of the principal strategies of innovation opportunity identification. This paper analyzes the findings of a two-year-long research project conducted in Riga Technical University with the data collection from different countries of Europe, Asia and America (n=1050) to explore whether there are principal differences in the perception of innovation opportunities by males and females. The qualitative content analysis of the respondents' texts revealed three groups of problems shared by males and females: 1) universal problems which are perceived similarly by both genders, 2) problems, which are perceived by males more, and 3) problems, which are perceived by females more. So, innovation opportunity identification is gender related.